Daily monitoring of the internal training load by the heart rate variability: A case study - Ornelas, Felipe; Nakamura, Fábio Y.; Dos-Santos, Julio W.; Batista, Danilo R.; Meneghel, Vlademir; Nogueira, Wagner J.; Brigatto, Felipe A.; Germano, Moisés D.; Sindorf, Márcio A.G.; Moreno, Marlene A.; Lopes, Charles R.; Braz, Tiago V. (My University, 2017)
The objective of this study was to present a descriptive case study with daily monitoring of the internal training load (ITL) according to the heart rate variability (HRV) in an amateur road running athlete. The subject was male (24 yrs old, 67.8 kg, 168 cm, %fat = 13%, 7 yrs of training, 3 times·wk-1 in the last 6 months, 6 to 7 hrs·wk-1) with no history of recent muscle, joint, or bone injury (< 6 months). The proposed training was of 12 sessions during 3 wks. The maximum aerobic speed (MAS), threshold HRV (ThHRV), and 1 maximum repetition (1RM) at the pre and post training moments were evaluated. The daily HRV monitoring was carried out according to the natural logarithm of the root mean square differences between adjacent normal R-R intervals (lnRMSSD), mean of the weekly lnRMSSD (lnRMSSDweekly), coefficient of variation of the weekly lnRMSSD (lnRMSSDcv), and division of the lnRMSSD by the R-R interval (lnRMSSD:RR). Improvements in MAS (11.5%), ThHRV (15.0%) and lnRMSSD (45.8%) were verified after 3 wks, and also in the 1RM for the brench press (5.0%), squatting (14.5%), knee extension (5.6%), and hamstring curl (14.8%) exercises. The descriptive values for weeks 1, 2, and 3 for the variables lnRMSSDweekly, ITL, lnRMSSDcv, and lnRMSSD:RR were 3.16, 3.98, and 4.02 ms, 1555, 1950, and 1808 a.u., 7.7, 10.2, and 11.9%, and 3.89, 4.38, and 4.06, respectively. The ITL was smaller in week 1 accompanied by a reduction in lnRMSSDcv. The change in lnRMSSDweekly (1 to 3 = 27%) was related to an improvement in the subject's performance. The individual analysis of the sessions by SWC allowed one to verify recovery periods (> lnRMSSD) and fatigue (< lnRMSSD) accompanied by increases or decreases in ITL. Week 2 caused more stress in the individual due to the tendency to increase vagal saturation (> lnRMSSD:RR) accompanied by a greater ITL.
Keywords: Autonomic nervous system; Running; Training load